Synthesis of Biochar-Like Graphene Nanosheets (BLG) from Candlenut Shells with Integrated Conductive and Antibacterial Functionalities - Samosir, Friscilla Romiduk; Yahya, Mohd Fakharul Zaman Raja; Siburian, Rikson (Indonesian Journal of Chemical Analysis (IJCA), 2025)
Graphene’s exceptional electrical, mechanical, and chemical properties have enabled breakthroughs in electronics, energy storage, and biomedicine, yet large-scale, low-cost, and sustainable production methods remain elusive. Here, we report a facile, scalable route to synthesize Biochar-Like Graphene Nanosheets (BLG) from candlenut shell biomass using activated carbon as a dual-function reducing agent and combustion inhibitor in a modified muffle furnace pyrolysis system. Structural analysis by X-ray diffraction and Fourier-transform infrared spectroscopy confirms the formation of defect-rich, low-oxygen sp² carbon networks, while scanning electron microscopy reveals wrinkled layered morphologies that promote electrolyte accessibility. Electrical measurements demonstrate a voltage-dependent conductivity, reaching 368.67 μS·cm⁻² at 1.5 V, alongside stable power density (6.72 W·kg⁻¹) and high energy density (403.2 Wh·kg⁻¹), indicative of excellent charge transport and storage capabilities. Remarkably, BLG exhibits potent antibacterial activity against Salmonella typhimurium with a 10.76 ± 0.23 mm inhibition zone and positive MIC and MBC responses, attributed to synergistic membrane disruption, reactive oxygen species generation, and electron transfer effects. This biomass-to-graphene strategy offers a sustainable, multifunctional nanomaterial platform for next-generation energy, environmental, and biomedical technologies